Chaetomium atrobrunneum causing human eumycetoma: The first report - Mhmoud, Najwa A. (PLoS Negl Trop Dis, 2019)
In this communication, a case of black grain eumycetoma produced by the fungus C. atrobrunneum is reported. The patient was initially misdiagnosed with M. mycetomatis eumycetoma based on the grains’ morphological and cytological features. However, further aerobic culture of the black grains generated a melanised fungus identified as C. atrobrunneum by conventional morphological methods and by internal transcribed spacer 2 (ITS2) ribosomal RNA gene sequencing. This is the first-ever report of C. atrobrunneum as a eumycetoma-causative organism of black grain eumycetoma. It is essential that the causative organism is identified to the species level, as this is important for proper patient management and to predict treatment outcome and prognosis.